ICT Method for Evaluation of Heritage Buildings Conservation. (2016) - Virtudes, Ana; Almeida, Filipa
Abstract: Historical buildings, such as vernacular architecture typologies, have been threatened by the vulnerability to their status degradation. This problem is not an exception in Portugal, where the few remaining examples of wooden stilt-houses, along Tagus river banks, have been neglected, with the disappearance or abandonment of almost all buildings, weakening the European cultural map. In Europe has been observed a growing concern in order to develop methods, tools and instruments for the management of current buildings stock, especially focused on housing, in order to improve their performances. However, these methods are don't fit in the features of traditional buildings such as wooden houses of vernacular architecture. In this sense, this research presents the detailed methodology used for the creation of an ICT (information and communication technology) method, especially designed for the evaluation of status of historical buildings conservation. It is focused on the explanation of its two main tools: the diagnosis record and the software. The results are an exhaustive survey of buildings features, useful as guideline for spatial planning strategies and instruments to protect this legacy. The proposed ICT method can be used in other similar buildings, and therefore to define best rehabilitation actions.